VITAMIN D RECEPTOR (VDR) GENE POLYMORPHISM AND MATERNAL VITAMIN D DEFICIENCY IN INDIAN WOMEN WITH PRETERM BIRTH (PTB) - Patel, Hitesh V; Patel, Nayana H; Sodagar, Nilofar R (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Preterm birth (PTB) is the leading cause of high infant mortality and long-term disability in young children worldwide. Array of adverse maternal and fetal outcomes linked with vitamin D level and its associated vitamin D receptor (VDR) gene. We undertook this study to investigate the association between VDR gene polymorphism with vitamin D deficiency and PTB in West Indian pregnant women. Methods: A total of 72 women with PTB and 138 healthy mothers with uncomplicated normal delivery were selected from different regions of Gujarat, India. FokI and TaqI single nucleotide polymorphism (SNP) of VDR gene determined by polymerase chain reaction and restriction fragment length polymorphism. Vitamin D level was determined using enzyme-linked immunosorbent assay. Result: ff genotype (29.17% vs. 10.87%, p=0.002) and f allele (49.31% vs. 35.51%, p=0.006) frequency distributions of VDR FokI showed significantly (odds ratio=0.566, 95% confidence interval=0.368-0.870, p=0.006) higher in women with preterm delivery than in control full term group. Genotype frequency of VDR TaqI showed no significant difference between preterm group and control. Conclusion: These results confirmed that women carrying ff genotype of FokI gene had significantly higher risk for vitamin D deficiency which enhances the risk of prematurity than women carrying FF genotype in West Indian women.